Laparoscopic versus Open End Colostomy Closure: A Single-center Experience. Issue 4 (April 2014) - Studer, Peter; SchnüRiger, Beat; Umer, Melika; KröLl, Dino; Inderbitzin, Daniel; Candinas, Daniel
The aim of this study was to review our experience with laparoscopic end colostomy closure. A retrospective review of a prospectively entered database was performed. Proportions and continuous variables were compared using the Fisher's exact and the Mann-Whitney U tests, respectively. Within the study period, 53 patients underwent closure of end colostomies. The main reasons for the colonic resections were perforated diverticulitis (52.7%) and neoplasms (20.8%). In 28 patients (53%), laparoscopic closure (LC) was attempted. Demographics did not differ between the attempted LC and the primary open closure (OC) group. The conversion rate from an LC to an OC was 50 per cent (14 of 28), mostly as a result of adhesions (71.4%). Hospital length of stay (HLOS) was significantly longer for the OC than with the attempted LC group (15.4 ± 11.9 days vs 11.3 ± 8.5 days, P = 0.046). The overall complication rate was not different between the completed LC and the OC groups (43 vs 56%, P = 0.634). The majority of complications detected (91.1%) were minor and could be treated conservatively. The role of laparoscopy to close end colostomies is questionable, because the conversion rate is high. However, a shorter HLOS can be expected when laparoscopy is successful. To reduce morbidity resulting from prolonged operation times, it is crucial to convert early and pre-emptively if hostile adhesions are found.